Jobs' Amenability to Working from Home : Evidence from Skills Surveys for 53 Countries - Hatayama, Maho; Viollaz, Mariana; Winkler, Hernan (World Bank, Washington, DC, 2020)
The spread of COVID-19 and implementation of "social distancing" policies around the world have raised the question of how many jobs can be done at home. This paper uses skills surveys from 53 countries at varying levels of economic development to estimate jobs' amenability to working from home. The paper considers jobs' characteristics and uses internet access at home as an important determinant of working from home. The findings indicate that the amenability of jobs to working from home increases with the level of economic development of the country. This is driven by jobs in poor countries being more intensive in physical/manual tasks, using less information and communications technology, and having poorer internet connectivity at home. Women, college graduates, and salaried and formal workers have jobs that are more amenable to working from home than the average worker. The opposite holds for workers in hotels and restaurants, construction, agriculture, and commerce. The paper finds that the crisis may exacerbate inequities between and within countries. It also finds that occupations explain less than half of the variability in the working-from-home indexes within countries, which highlights the importance of using individual-level data to assess jobs’ amenability to working from home.